2014
DOI: 10.2323/jgam.60.163
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of Candida albicans biofilms to fluconazole by terpenoids of plant origin

Abstract: Infections associated with the biofilms of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 22 publications
4
38
0
Order By: Relevance
“…The most significant IC 50 values were ranging 0.063-1.23 μM against C. krusei, C. glabrata, and C. albicans [38]. Fractional inhibitory concentration indices (FICI) for carvacrol-fluconazole and eugenolfluconazole combinations for C. albicans biofilm formation were 0.311 and 0.25, respectively [39]. Eugenol treatment significantly reduced the adherence and metabolic activity of biofilms of C. albicans isolated from the oral cavity of HIV infected patients [40].…”
Section: Antifungal Activity Of Eugenolmentioning
confidence: 99%
“…The most significant IC 50 values were ranging 0.063-1.23 μM against C. krusei, C. glabrata, and C. albicans [38]. Fractional inhibitory concentration indices (FICI) for carvacrol-fluconazole and eugenolfluconazole combinations for C. albicans biofilm formation were 0.311 and 0.25, respectively [39]. Eugenol treatment significantly reduced the adherence and metabolic activity of biofilms of C. albicans isolated from the oral cavity of HIV infected patients [40].…”
Section: Antifungal Activity Of Eugenolmentioning
confidence: 99%
“…Previous investigations demonstrated that carvacrol is one of the potent monoterpenes against C. albicans, impeding the growth of different morphological forms, including yeast, hyphae, and the highly drug-resistant biofilm (9)(10)(11). Recent studies have shown that the monoterpenes carvacrol and eugenol, but not thymol, synergize with the azole antifungal fluconazole and inhibit planktonic growth and biofilm in clinical resistant strains (12). Interestingly, carvacrol has been proved to be an effective treatment against vaginal candidiasis in an immunosuppressed rat model (13).…”
mentioning
confidence: 99%
“…In vitro studies have shown satisfactory results regarding the association between natural products and conventional antimicrobials directed for antifungal therapy [13][14][15]. In a study conducted in India [15], the authors showed that the addition of eugenol and carvacrol to fluconazole have significantly reduced the concentration of the latter, in inhibition of biofilm growth by C. albicans.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in India [15], the authors showed that the addition of eugenol and carvacrol to fluconazole have significantly reduced the concentration of the latter, in inhibition of biofilm growth by C. albicans. According to the aforementioned study, these terpenes cause instability in the fungal membrane and intervention in specific signals, facilitating greater fluconazole influx to the intracellular environment and culminating in inhibition of biofilm formation [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation